Why People Who Have Sex with Animals Believe That It Is Their Sexual Orientation—A Grounded Theory Study of Online Communities of Zoophiles. Issue 11 (2nd November 2018) - Sendler, Damian Jacob
ABSTRACT: This study explores online spaces of zoophiles. Relevant discussion forums, specializing in mental health, were identified through having threads on "sexuality, " "paraphilias, " and "zoophilia." Thematic analysis includes responses of 138 participants (135 exclusive zoophiles, and three zoophiles with pedophilic tendencies). Trend analysis identified most frequently discussed topics: animals as an object of love; emotional closeness with animals; what are paraphilias; can animals consent to sex with humans; misunderstanding terminology of zoophilia/bestiality. First, zoophiles frequently ask why zoophilia is considered an act of bestiality if the term to them means "to murder." Second, zoophiles believe that animals have an intrinsic ability to consent to sexual behaviors involving people. Third, most messages pointed to the lack of emotional support from the family and widespread public contempt.